HUBUNGAN ANTARA CARDIORESPIRATORY FITNESS DENGAN AKTIVITAS FISIK PADA SISWA SEKOLAH SEPAK BOLA METRO KUKUSAN DEPOK USIA 10-14 TAHUN - Raihan Nurihsan (2023)
Background: Cardiorespiratory fitness is or is often referred to as physical fitness which is influenced by many factors, one of which is physical activity. Physical activity is any bodily movement produced by skeletal muscles that requires energy expenditure. In accordance with what has been said, among the important goals of physical education is the achievement of several aspects of physical fitness which affect the ability of adolescents to carry out physical activities properly. To analyze and find out the relationship between cardiorespiratory fitness and physical activity in students at the Metro Kukusan Depok football school aged 10 - 14 years. Method: The method used in this research is correlational. The number of samples used in this study were 73 students from the Metro Kukusan Soccer School, Depok. The parameters used in measuring Cardiorespiratory Fitness are the Three minute step test and the IPAQ questionnaire is used to measure physical activity. Results: This study used SPSS 25 and based on the results of research on 73 students, found 38 students with moderate physical activity (≥600 MET <3000) (52%) and YMCA-3MST average of 24 students (32.8%). The results of the Spearman correlation test showed P Value = 0.001 so that the two variables namely Cardiorespiratory Fitness and physical activity have a relationship. Conclusion: In this study, it was found that there was a relationship between cardiorespiratory fitness and physical activity in SSB Metro Kukusan Depok students aged 10-14 years.